1989
DOI: 10.1105/tpc.1.3.313
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the glycinin gene family in soybean.

Abstract: We characterized the structure, organization, and expression of genes that encode the soybean glycinins, a family of storage proteins synthesized exclusively in seeds during embryogenesis. Five genes encode the predominant glycinin subunits found in soybeans, and they have each been cloned, sequenced, and compared. The five genes have diverged into two subfamilies that are designated as Group-I and Group-II glycinin genes. Each glycinin gene contains four exons and three introns like genes that encode related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(92 citation statements)
references
References 74 publications
1
91
0
Order By: Relevance
“…Further analysis of soybean glycinin structure in comparison with similar legume proteins reveals that the epitopes reported here may be located in a particularly allergenic region of legume seed storage proteins. The primary structure of glycinin, in comparison with similar legume family proteins, possesses three variable regions [24]. These regions have been identified as residing at the surface of the glycinin subunit since proteolytic cleavage occurs at or near these variable regions [24, 29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further analysis of soybean glycinin structure in comparison with similar legume proteins reveals that the epitopes reported here may be located in a particularly allergenic region of legume seed storage proteins. The primary structure of glycinin, in comparison with similar legume family proteins, possesses three variable regions [24]. These regions have been identified as residing at the surface of the glycinin subunit since proteolytic cleavage occurs at or near these variable regions [24, 29].…”
Section: Discussionmentioning
confidence: 99%
“…The primary structure of glycinin, in comparison with similar legume family proteins, possesses three variable regions [24]. These regions have been identified as residing at the surface of the glycinin subunit since proteolytic cleavage occurs at or near these variable regions [24, 29]. Both epitope A and epitope B reside in a domain between two variable regions (variable region 2, residues Q188–E216, and the hypervariable region, residues T269–K306 [24]) that may represent a particularly allergenic domain of legume seed storage proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have already concluded that seed composition can be strongly affected by genetic and environmental factors and that the genetic background of each variety controls seed composition and how much of the multi-subunit storage proteins contribute for total seed protein of soybeans (Krishnan, 2001;Nielsen et al, 1989;Zarkadas et al, 2007).…”
Section: Soybeanmentioning
confidence: 99%